Prediction Error of Intraocular Lens Power Calculation in Very Elderly Patients over 90 Years Old. (3rd August 2021) - Koga, Yusuke; Kojima, Kentaro; Yoshii, Kengo; Kusada, Natsuki; Kagitani, Yu; Aoki, Takanori; Horiuchi, Noriko; Kitazawa, Koji; Sotozono, Chie
ABSTRACT: Background: To investigate the influence of age on prediction error (PE) after cataract surgery in very elderly (VE) patients aged more than 90 years. Methods: We retrospectively analyzed 66 eyes of patients aged ≥90 years (VE group) who underwent phacoemulsification and intraocular lens (IOL) implantation. As the control group (CG), we investigated 121 eyes of patients aged 70–89 years who underwent the same surgery. PE was calculated 1 month post-surgery as the actual postoperative spherical equivalent minus the target diopter, which was calculated using the Sanders–Retzlaff–Kraff/T formula. The absolute and arithmetic PE were compared between the two groups. The factors affecting absolute PE outside ±0.5 diopter (D) and ±1.0 D were determined through logistic regression analysis with the variables age, sex, axial length (AL), average corneal power, preoperative best-corrected visual acuity, target diopter, and coexisting pseudoexfoliation syndrome. Results: The absolute PE was significantly larger in the VE group than that in the CG (0.60 ± 0.52 D and 0.34 ± 0.25 D, respectively; P < .001). There was no significant difference in terms of arithmetic PE between the two groups (−0.06 ± 0.79 D and −0.07 ± 0.42 D, respectively; P = .653). In the logistic regression analysis, age was significantly associated with absolute PE outside ±0.50 D (Odds ratio [OR]: 1.05). Age and AL were significantly associated with absolute PE outside ±1.0 D (OR: 1.24 and 0.20, respectively). Conclusions: Absolute PE tended to increase in the cataract surgery of VE patients.